Bridging academician and community through knowledge transfer program (KTP) on workplace risk assessment technique- A case study - Nur Fazlinna, Ab Ghani; Azizan, Ramli; Kharul Anwar, Johari; Mohd Shaiful Zaidi, Mat Desa; Norhaslinda, Hanapi (Penerbit Universiti Malaysia Pahang, 2021)
Since technical education involves equipment and workshop/laboratory activities, safety and health risks due to hazardous situations have become the primary issue and require immediate mitigation measures. The main issue that needs immediate attention here is that most ADTEC (Advanced Technology Training Center) staff lack expertise in workplace risk assessment techniques. Some of them are also unaware of these life-threatening safety and health risks. They are unable to anticipate the long-term impact of their everyday activities on their safety and health. Thus, knowledge of hazard identification and prevention strategies is essential for them to improve their workplace environment. This program has been executed in four stages, which are off-the-job training, walkabout and hands-on activity, oral presentation, and followed by an individual assessment. As for an individual assessment, all participants need to sit the written test and an oral interview. The purpose of an individual assessment is to gauge participant understanding and the effectiveness of the program. The program has been conducted successfully whereby all the 32 participants have undergone the training and passed the assessment (written test and interview). All participants gave very encouraging feedback and believed this program would equip them with knowledge on conducting the risk assessment for all activities in their organization. The authors strongly believe that this initiative and program will ultimately assist ADTEC in reducing the probability of accident occurrence in their organization.